Private Justice : Deceived - Book 3 - Hannon, Irene (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2014)
"For three years, Kate Marshall has been grieving the loss of her husband and their four-year-old son in a boating accident. But when she spots a familiar-looking child on an escalator in the mall, she is convinced it is the son she thought was dead. With police skeptical of her story, she turns to private investigator Connor Sullivan. The former Secret Service agent is dubious but agrees to investigate. Digging into the case he discovers that the incident may have been no accident at all"--Amazon.com.
Keywords: Women journalists -- Fiction; Private investigators -- Fiction; Missing persons -- Fiction -- Investigation; Mystery fiction